2023
DOI: 10.3389/fpls.2023.1151762
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and highly efficient morphogenic gene-mediated hexaploid wheat transformation

Abstract: The successful employment of morphogenic regulator genes, Zm-Baby Boom (ZmBbm) and Zm-Wuschel2 (ZmWus2), for Agrobacterium-mediated transformation of maize (Zea mays L.) and sorghum (Sorghum bicolor L.) has been reported to improve transformation by inducing rapid somatic embryo formation. Here, we report two morphogenic gene-mediated wheat transformation methods, either with or without morphogenic and marker gene excision. These methods yield independent-transformation efficiency up to 58% and 75%, respective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…This is a significant increase from the biolistic-mediated transformation (0.1%-1%) previously used in our study (Xu et al, 2022). Similarly to the recently developed "QuickWheat" transformation method with overexpression of maize WUS and BBM genes (Johnson et al, 2023), we observed a low 5% escape rate on hygromycin selection, as confirmed by PCR. The quality of transgenic events was evaluated by estimating the transgene copy number and integrity of the T-DNA borders.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…This is a significant increase from the biolistic-mediated transformation (0.1%-1%) previously used in our study (Xu et al, 2022). Similarly to the recently developed "QuickWheat" transformation method with overexpression of maize WUS and BBM genes (Johnson et al, 2023), we observed a low 5% escape rate on hygromycin selection, as confirmed by PCR. The quality of transgenic events was evaluated by estimating the transgene copy number and integrity of the T-DNA borders.…”
Section: Discussionsupporting
confidence: 74%
“…Until recently, the stable wheat transformation was relatively challenging due to its high variability and genotype-dependency, resulting in low transformation efficiency (1%–2%). The delivery of growth-regulating and regeneration-related genes such as TaWox5 ( Wang et al, 2022 ), maize Zm-Baby Boom ( ZmBbm ) and Zm-Wuschel2 ( ZmWus2 ) ( Johnson et al, 2023 ), and GROWTH-REGULATING FACTOR 4 ( GRF4 ) and its cofactor GRF-INTERACTING FACTOR 1 ( GIF1 ) GRF–GIF ( Debernardi et al, 2020 ) results in a significant boost in transformation efficiency ranging from 58% to 75%. Although higher transformation efficiency allows for reproducible generation of transgenic plants carrying the CRISPR/Cas9 constructs in different experiments, editing efficiency at different loci still varies significantly.…”
Section: Introductionmentioning
confidence: 99%
“…A study performed with transgenic maize and soybean found that transgene expression levels were mainly impacted by the choice of promoter and the choice of genetic background cultivar, while the genomic site of transgene insertion played a minor role ( Betts et al , 2019 ). Recent technological progress enables the transformation of any wheat genotype of interest ( Debernardi et al , 2020 ; Wang et al , 2022 ; Johnson et al , 2023 ), which greatly facilitates the testing of transgenes in different genetic backgrounds. In this study we used a combined approach of transgene insertion by biolistic transformation and subsequent cross-breeding to generate plants overexpressing two pyramided NLR type of resistance genes from the primary and the tertiary gene pool of wheat.…”
Section: Discussionmentioning
confidence: 99%
“…Morphogenic regulators are instrumental in improving tissue culture. For instance, overexpressing these genes promotes somatic embryo formation without additional hormones (Gordon‐Kamm et al, 2019; Horstman et al, 2017; Lian et al, 2022; Liu et al, 2014; Lowe, et al, 2016; Yarra & Krysan, 2023) and significantly enhances the transformation efficiency in monocotyledonous plants, including maize, sorghum, sugarcane, and rice (Duan et al, 2022; Johnson et al, 2023; Kausch et al, 2021; Mookkan et al, 2017; Nalapalli et al, 2021; Nelson‐Vasilchik et al, 2022; Zhou et al, 2022; Lowe et al, 2016). Furthermore, the recent development of the non‐invasive reporter RUBY has facilitated screening in genetically transformed plants by producing a red coloring (He et al, 2020; Yu et al, 2023).…”
Section: Introductionmentioning
confidence: 99%